Vulnerability analysis in complex networks under a flood risk reduction point of view - Santos, Leonardo B. L.; Soares, Giovanni G.; Garg, Tanishq; Jorge, Aurelienne A. S.; Londe, Luciana R.; Reani, Regina T.; Bacelar, Roberta B.; Oliveira, Carlos E. S.; Freitas, Vander L. S.; Sokolov, Igor M. (Frontiers in Physics, 2023)
The measurement and mapping of transportation network vulnerability to natural hazards constitute subjects of global interest for a sustainable development agenda and as means of adaptation to climate change. During a flood, some elements of a transportation network can be affected, causing the loss of lives. Furthermore, impacts include damage to vehicles, streets/roads, and other logistics services - sometimes with severe economic consequences. The Network Science approach may offer a valuable perspective considering one type of vulnerability related to network-type critical infrastructures: the topological vulnerability. The topological vulnerability index associated with an element is defined as reducing the network’s average efficiency due to removing the set of edges related to that element. In this paper, we present the results of a systematic literature overview and a case study applying the topological vulnerability index for the highways in Santa Catarina (Brazil). We produce a map considering that index and areas susceptible to urban floods and landslides. Risk knowledge, combining hazard and vulnerability, is the first pillar of an Early Warning System and represents an important tool for stakeholders of the transportation sector in a disaster risk reduction agenda.